1964
DOI: 10.4039/ent96377-1
|View full text |Cite
|
Sign up to set email alerts
|

Insect Mycetomes

Abstract: After defining the entomological use of the term mycetome a short general account is given of the various supposedly beneficial relationships between insects and internally harboured micro-organisms and the metabolic balance needed. Not all beneficial micro-organisms are harboured in mycetomes or even in mycetocytes, but the present paper is concerned only with insects having mycetomes. It is shown that there is good evidence for accepting the premise that true micro-organisms are found in insect mycetomes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1966
1966
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Further the passage from midgut to hindgut is surrounded with two pairs of malphigian tubules. Mycetome is a specialized structure that comprises a group of either gut cells or fat cells 34 . In some hemipterans such as whiteflies and aphids the mycetome or bacteriocytes are present as a separate organ within the abdomen, but not as a part of the alimentary canal.…”
Section: Discussionmentioning
confidence: 99%
“…Further the passage from midgut to hindgut is surrounded with two pairs of malphigian tubules. Mycetome is a specialized structure that comprises a group of either gut cells or fat cells 34 . In some hemipterans such as whiteflies and aphids the mycetome or bacteriocytes are present as a separate organ within the abdomen, but not as a part of the alimentary canal.…”
Section: Discussionmentioning
confidence: 99%
“…Singh & Musgrave (1966), using the tannic acid/crystal violet technique for lightmicroscope studies, have found evidence of a distinct cell-wall-like membrane around some of the mycetomal micro-organisms of S. granarius, and indications of a plasma membrane. But the micro-organisms are pleomorphic and may have some kind of life-cycle (Musgrave, 1964). It is also possible that some of them have become almost a part of the host cell, or may be dying or dead, or being lysed by the host cell with consequent loss of the outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The weevil Sitophilus granarius (L.), in the GG strain (Musgrave, 1964), harbours certain characteristic micro-organisms in larval mycetomes (the latest work on the Sitophilus-Calandra synonymy and their species appears to be that of Kuschel (1961)). The mycetomes break up at metamorphosis, as in Sitophilus oryzae (L.) (Murray & Tiegs, 1935), and the micro-organisms are found in adult mesentera and female gonads.…”
Section: Introductionmentioning
confidence: 99%
“…The mycetomes break up at metamorphosis, as in Sitophilus oryzae (L.) (Murray & Tiegs, 1935), and the micro-organisms are found in adult mesentera and female gonads. The mycetomal micro-organisms are thought, as in some other insects (Buchner, 1953), to benefit the host weevil nutritionally (Musgrave, 1964) and are said to be inherited through the female (Koch, 1956;Musgrave & Miller, 1956). Their identity has not definitely been established (Musgrave & Miller, 1958) and they have so far, like many similar symbiotes (Brooks, 1963;Koch, i960), resisted culture (Musgrave & McDermott, 1961).…”
Section: Introductionmentioning
confidence: 99%